The importance of aerobic fitness for tennis: a review (part 2) - Genevois, C. (Coaching and Sport Science Review, 2019)
In part 1 of this series we discussed why aerobic fitness is important for tennis players (Genevois, 2019). Scientific studies have revealed that High Intensity Intermittent Training (HIIT) is an efficient way to improve aerobic fitness either off- or on-court, depending on the training phase. The intensity of the training sessions can be individualized based on the final speed reached during the 30/15 Intermittent Fitness Test.